Nociception and alpha2delta3 - Neely, Greg (Henry Stewart Talks, 2012)
Finding key conserved pain genes in drosophila as a model for human genes, Finding conserved regulators of nociception, Assay for nociception in adult flies, Painless mutant flies & noxious temperatures, Genome wide nociception screen in adult fly, Human GWAS for chronic pain gene, Alpha-2-delta-3 (Straightjacket = stj) as a novel acute & chronic pain gene and the effect on its manipulation in mice and flies